Phytochemical profiling and fractionation of Helianthemum lippii extract versus silver nanoparticle-modified extract: assessment of photoprotective, anti-hemolytic, antibacterial, and anti-inflammatory properties - Laib, Ibtissam; Boutlilis, Djahra Ali; Alsaeedi, Huda; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
Introduction This study investigates the synthesis of silver nanoparticles (Ag NPs) using Helianthemum lippii extract and evaluates their photoprotective, anti-hemolytic, antibacterial, and anti-inflammatory properties compared to various extract fractions, including total aqueous extract (AE), flavonoid monoglycosides (FMG), flavonoid diglycosides/triglycosides (FDG/FTG), tannins (TN), and anthocyanins (AC). Helianthemum lippii is rich in bioactive compounds such as caffeic acid, p-coumaric acid, and gallic acid, known for their therapeutic potential. This study aims to determine whether embedding these phytochemicals into Ag NPs enhances their biomedical applications compared to the natural extract fractions. Methods Ag NPs were synthesized using Helianthemum lippii extract through a green synthesis approach, and their physicochemical properties, including size and morphology, were characterized. High-performance liquid chromatography (HPLC) was used to identify key phytochemicals in the various extract fractions. Biological assays were conducted to assess photoprotective efficacy (sun protection factor, SPF), antibacterial activity (minimum inhibitory concentration, MIC), anti-inflammatory potential (percentage inhibition), and hemolytic properties, with sodium dodecyl sulfate (SDS) serving as a control. Results HPLC analysis confirmed the presence of bioactive compounds, including caffeic acid, p-coumaric acid, and gallic acid, in the AE extract. The Ag NPs were spherical with an average diameter of 35 nm and had phytochemicals adsorbed on their surface. The AC fraction demonstrated the highest SPF (28.27), followed by TN (27.99), AE (23.20), and Ag NPs (22.50), while FMG exhibited a moderate SPF (19.39) compared to the commercial sunscreen Avene® (40.00). Ag NPs exhibited superior antibacterial activity with MIC values of 0.2 mg/mL against Pseudomonas aeruginosa and 0.4 mg/mL against Bacillus subtilis, outperforming AE, which had a MIC of 2.81 mg/mL. Anti-inflammatory assays showed that Ag NPs achieved 79.8% inhibition at 400 μg/mL, surpassing AE (71.75%) and TN (67.9%), and were comparable to diclofenac (72.63%). Hemolysis assays revealed that Ag NPs induced only 1.35% hemolysis, lower than AE (1.91%) and significantly below SDS (90.48%). Discussion The findings demonstrate that Helianthemum lippii-derived Ag NPs exhibit enhanced antibacterial, anti-inflammatory, and anti-hemolytic properties compared to the extract fractions. While the SPF of Ag NPs was slightly lower than the AC and TN fractions, their superior multifunctional bioactivities underscore their potential for various biomedical applications. The integration of phytochemicals into Ag NPs significantly enhances their therapeutic efficacy, making them promising candidates for advanced pharmaceutical formulations and topical protective agents.